The influence of adolescent nicotine exposure on ethanol intake and brain gene expression. - Constanza P Silva; William J Horton; Michael J Caruso; Aswathy Sebastian; Laura C Klein; Istvan Albert; Helen M Kamens (PLoS ONE)
Nicotine and alcohol are often co-abused. Adolescence is a vulnerable period for the initiation of both nicotine and alcohol use, which can lead to subsequent neurodevelopmental and behavioral alterations. It is possible that during this vulnerable period, use of one drug leads to neurobiological alterations that affect subsequent consumption of the other drug. The aim of the present study was to determine the effect of nicotine exposure during adolescence on ethanol intake, and the effect of these substances on brain gene expression. Forty-three adolescent female C57BL/6J mice were assigned to four groups. In the first phase of the experiment, adolescent mice (PND 36-41 days) were exposed to three bottles filled with water or nicotine (200 μg/ml) for 22 h a day and a single bottle of water 2 h a day for six days. In the second phase (PND 42-45 days), the 4-day Drinking-in-the-Dark paradigm consisting of access to 20% v/v ethanol or water for 2h or 4h (the last day) was overlaid during the time when the mice did not have nicotine available. Ethanol consumption (g/kg) and blood ethanol concentrations (BEC, mg %) were measured on the final day and whole brains including the cerebellum, were dissected for RNA sequencing. Differentially expressed genes (DEG) were detected with CuffDiff and gene networks were built using WGCNA. Prior nicotine exposure increased ethanol consumption and resulting BEC. Significant DEG and biological pathways found in the group exposed to both nicotine and ethanol included genes important in stress-related neuropeptide signaling, hypothalamic-pituitary-adrenal (HPA) axis activity, glutamate release, GABA signaling, and dopamine release. These results replicate our earlier findings that nicotine exposure during adolescence increases ethanol consumption and extends this work by examining gene expression differences which could mediate these behavioral effects.